Pengaruh Program Latihan Refleks Primitif Terhadap Kemampuan Motorik pada Anak Tunadaksa di SLBN Prof. Sri Soedewi Kota Jambi - Wanti Hasmar; Faridah Faridah (Science: Indonesian Journal of Science, 2026)
Children with physical disabilities, particularly those with spastic cerebral palsy (CP), often exhibit persistent primitive reflexes that impair postural control, balance, coordination, and motor development. A primitive reflex exercise program is an approach aimed at integrating these persistent reflexes to enhance motor skills. This study aimed to analyze the effect of a primitive reflex exercise program on the motor skills of children with physical disabilities at SLBN Prof. Sri Soedewi, Jambi City. A quasi-experimental design with a non-equivalent control group approach was employed. The study sample consisted of 14 children with physical disabilities and spastic CP, aged 7–12 years, selected via total sampling. Motor skills were measured using the Gross Motor Function Measure (GMFM-88). Data analysis was performed using the Paired Sample t-test with a significance level of 5%. The results showed that the mean motor skill score was 45.30 ± 8.12 prior to the intervention and increased to 58.75 ± 9.26 following the primitive reflex exercise program. Statistical analysis yielded a p-value of 0.000 (p < 0.05), indicating a significant effect of the primitive reflex exercise program on improving the motor skills of children with physical disabilities. In conclusion, the primitive reflex exercise program is effective in enhancing motor skills among children with physical disabilities at SLBN Prof. Sri Soedewi, Jambi City.